Heterogeneous impact of anti-bullying laws on school bullying in the State of Georgia - Mona Ahmadiani; Pourya Valizadeh; Genti Kostandini; Jeffrey L. Jordan (PLoS ONE, 2025)
The increasing prevalence of bullying behavior has made anti-bullying laws (ABL) and policies a public health priority in the United States. Using 2007–2016 data from the Georgia Student Health Survey 2.0 on 6–12 grade public school students, we examine the relationship between two ABLs—with different levels of stringency—and the prevalence of bullying behavior in the state of Georgia. We find that although the implementation of both Georgia’s ABLs is associated with significant declines in the prevalence of bullying victimization, the more stringent ABL is associated with substantially larger reductions in reported cases. Our heterogeneity analysis based on external environment characteristics shows that the more stringent ABL is associated with smaller reductions in bullying victimization incidents in schools with a higher share of students enrolled in the federally subsidized school lunch program. The more stringent ABL is also associated with larger increases in bystanders’ willingness to intervene in school districts with higher poverty rates among children aged 5–17. Lastly, we analyze disparities in bullying victimization reporting at the school level and find that students tend to report higher bullying victimization rates than school personnel, and that the two ABLs are associated with larger reductions in the student reporting than in personnel reporting. Our results also show that the reporting disparities fade away when ABLs are in place, providing further evidence of the role of ABLs in mitigating bullying victimization reporting discrepancies.